Politics as a Science A Prolegomenon - Schmitter, Philippe (Taylor & Francis, 2020)
"In Politics as a Science, two of the world's leading authorities on comparative politics, Philippe C. Schmitter and Marc Blecher, provide a lively introduction to the concepts and framework to study and analyze politics. Written with dexterity, concision and clarity, this short text makes no claim to being scientific. It contains no disprovable hypotheses, no original collection of evidence, and no search for patterns of association. Instead, Schmitter and Blecher keep the text broadly conceptual and theoretical to convey their vision of the sprawling subject of politics. They map the process in which researchers try to specify the goal of the trip, some of the landmarks likely to be encountered en route, and the boundaries that will circumscribe the effort. Examples, implications and elaborations are included in footnotes throughout the book. Politics as a Science is an ideal introduction for anyone interested in, or studying, comparative politics."